Inquiry in a Science Museum: Science Museum Educators' Views and Practices - Maria Karnezou; Petros Kariotoglou (MDPI AG, 2022)
Our study looks into science museum educators' views and their practices about inquiry in non-formal venues, such as NOESIS, Greece. On this ground, we developed an interview protocol to use as a basis in the semi-structured interviews conducted with four science museum educators to cast light on their views about inquiry. In addition, an observation protocol was modified in order to observe their practices when implementing educational programs for school groups. Data analysis showed that in regard to the museum educators' views, they all expressed a slightly different view about inquiry, which was either empirically or intuitively based. They all agreed that inquiry is easier adopted in non-formal settings and argued that students' main gain when they get engaged in inquiry-based activities is the actual involvement they experience. As regards the museum educators' practices, a repertoire of teaching approaches was observed, ranging from a traditional teacher-centered approach to open inquiry. Building on our data, we suggest the development and implementation of a professional development course that will enrich science museum educators' inquiry views and practices and empower them to integrate inquiry-based practices into their own.